The Relationship between Modification of Food Presentation and Changes in Appetite of Toddler Children at Puskesmas Mojo Surabaya - Anggraini, Refida Fitria; Ananditha, Aries Chandra; Aminoto, Latifiyan Nurnaningtiyas; Illiandri, Oski (Universitas Muhammadiyah Semarang, 2016)
Background: Modification of food presentation is one way to attract toddlers to increase their appetite with attractive colors or cute shapes to increase the child's appetite. Modification of food presentation can also affect appetite changes in children under five, so it takes a unique and exciting food creation that can be an attraction/pleasure for children under five to increase appetite. Children's stability under five depends a lot on their parents or caregivers because the parents must be the main scourge / main factor in increasing the child's appetite. So, it can be said that the development of children under five is very dependent on how their parents manage their child's food—providing a variety of foods, especially vegetables, which children usually do not like so that they become liked by them. There are many things or ways to attract toddlers to like vegetables, namely by adding side dishes that have been mixed with vegetables and rice that can be cooked and mixed with coloring from the vegetables themselves. Objective: To explore the relationship between food presentation modification and appetite changes for children under five at Puskesmas Mojo Surabaya.Method: Analytical Cross-Sectional Observational Research DesignResult: Most of the modification of food presentation for children under five at Puskesmas Mojo Surabaya received it well. Changes in appetite for children under five at Puskesmas Mojo Surabaya are mostly changes in appetite.Conclusion: There is a relationship between modification of food presentation and appetite changes for children under five at Puskesmas Mojo Surabaya.